Neurodevelopmental Outcome of High Risk Babies at One Year of Age Born in a Tertiary Centre - Shrestha, Merina; Bajracharya, Luna; Shrestha, Laxman (Journal of Nepal Paediatric Society, 2017)
Introduction: With increasing survival of high risk babies, children with different developmental disabilities have emerged as a challenge for the baby, family as well as for physicians. With limited awareness and resources, follow-up and interventions for these babies are difficult. The study was carried out to find out the development of high risk babies in different developmental domains at one year of age. Material and Methods: NICU graduates who visited high risk clinic at one year of age were assessed. ASQ-3 was used to screen development. Children with major congenital anomalies and syndromes were excluded from the study. Results: Out of 28 high risk babies, about 29% had global delay. Those babies who had seizure during neonatal period could not score even in single item of ASQ-3. Conclusion: All high risk babies are at risk of developing delay hence should be followed up regularly. Timely early intervention needs to be started to minimize delay.